Empirical Analysis of the Relationship between Corruption, Law Enforcement, Economic Growth, and Foreign Direct Investment in Indonesia - Indriya Fathni; Yana Priyana; Erry Fitrya Primadhany (Westscience Press, 2023)
The link between corruption, law enforcement, economic progress, and foreign direct investment (FDI) in Indonesia is the subject of an experimental inquiry in this article. When elements like trade openness, human capital, and infrastructure development are considered, such as their effects on economic growth and FDI inflows, the study employs multiple regression analysis to examine the influence of crime and law enforcement on these two variables. The study's findings show that law enforcement and corruption significantly impact Indonesia's FDI inflows and economic growth. Law enforcement has a favorable effect on both economic growth and FDI inflows, while sin has the opposite effect. The findings suggest that reducing crime and bolstering law enforcement are essential to promoting economic growth and enticing foreign investment in Indonesia.